2016
DOI: 10.1002/2015jg003239
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impacts of tillage and fertilization management on nitrous oxide emissions in a cornfield using the DNDC model

Abstract: Quantification and prediction of N2O emissions from croplands under different agricultural management practices are vital for sustainable agriculture and climate change mitigation. We simulated N2O emissions under tillage and no‐tillage,and different nitrogen (N) fertilizer types and application methods (i.e., nitrification inhibitor, chicken manure, and split applications) in a cornfield using the DeNitrification‐DeComposition (DNDC) model. The model was parameterized with field experimental data collected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 57 publications
(100 reference statements)
2
28
0
Order By: Relevance
“…Since both SOC and N2O emissions were well-validated in North America [40][41][42][43][44][45][46][47][48], and the "out of the box" approach has demonstrated its consistency with field studies [52], we believe that our approach and use of the model is reasonable in this case. In this study, we used the DNDC model to estimate the impacts of conservation management practices on SOC dynamics and N2O emissions across 645 counties in the Corn Belt from 2005 to 2018, based on OpTIS mapping results.…”
Section: Study Areamentioning
confidence: 82%
See 1 more Smart Citation
“…Since both SOC and N2O emissions were well-validated in North America [40][41][42][43][44][45][46][47][48], and the "out of the box" approach has demonstrated its consistency with field studies [52], we believe that our approach and use of the model is reasonable in this case. In this study, we used the DNDC model to estimate the impacts of conservation management practices on SOC dynamics and N2O emissions across 645 counties in the Corn Belt from 2005 to 2018, based on OpTIS mapping results.…”
Section: Study Areamentioning
confidence: 82%
“…Jarecki et al [43] also reported that the modeled and observed SOC were in good agreement at both sites in Canada, with differences ranging from 0.39 to 4.1 Mg C ha −1 . DNDC has also been validated against N 2 O flux and N leaching measurement data in North America (i.e., USA and Canada), Europe (i.e., Belgium, UK), and East Asia (i.e., China, Japan, and Thailand) [44][45][46][47][48][49][50][51]. In addition, our previous study has compared the not-validated DNDC simulations of N 2 O emissions and N leaching in the Corn Belt with 56 peer-reviewed field studies of similar interventions, and the results showed that those simulations were consistent with the meta-analysis of Midwest corn N 2 O mitigation potential [52].…”
Section: Modeling Of Conservation Managementmentioning
confidence: 99%
“…In the LPJmL.G.Orig scenario, all management information as well as soil C and N pools were used as within the default global simulation of LPJmL (Table 3). The amount of mineral and organic fertilizers was provided by the global gridded crop model intercomparison (Elliott et al, 2015) of the Agricultural Model Intercomparison and Improvement Project (AgMIP; Rosenzweig et al, 2013). It is based on global, gridded data sets for each crop (Mueller et al, 2012;Potter et al, 2010).…”
Section: Lpjml Standard Setup Using Global Input Datamentioning
confidence: 99%
“…Investigating the confounding impacts of multiple environmental factors on N 2 O emissions is critical for enriching understanding of N 2 O production, emission, and mitigation (Deng et al. , Liu et al. ).…”
Section: Introductionmentioning
confidence: 99%